Durability of first ART regimen and risk factors for modification, interruption or death in HIV-positive patients starting ART in Europe and North America 2002-2009 - Abgrall, Sophie; Ingle, Suzanne M; May, Margaret T; Costagliola, Dominque; Mercie, Patrick; Cavassini, Matthias; Reekie, Joanne; Samji, Hasina; Gill, M John; Crane, Heidi M; Tate, Jan; Sterling, Timothy R; et al. (AIDS (London), 2013)
To estimate the incidence of and risk factors for modifications to first antiretroviral therapy (ART) regimen, treatment interruption and death. A total of 21 801 patients from 18 cohorts in Europe and North America starting ART on regimens including at least two nucleoside reverse transcriptase inhibitors and boosted protease inhibitor or non-nucleoside reverse transcriptase inhibitor during 2002-2009 were included. Incidence of modifications (change of drug class, substitution/addition within class, or switch to nonstandard regimen), interruption or death and associations with patient characteristics were estimated using competing-risks methods. During median 28 months follow-up, 8786 (40.3%) patients modified first ART, 2346 (10.8%) interrupted and 427 (2.0%) died before changing regimen. Three-year cumulative percentages of modification, interruption and death were 47, 12 and 2%, respectively. After adjustment, rates of interruption were highest for IDUs and lowest for MSM, and higher for patients starting ART with CD4 cell count above 350 cells/μl than other patients. Compared to efavirenz, patients on lopinavir and other protease inhibitors had higher rates of modification and interruption, on atazanavir had lower rates of class change, and on nevirapine higher rates of interruption. Those on tenofovir/emtricitabine backbone had lowest rates of substitutions and switches to nonstandard regimen, and on abacavir/lamivudine lowest rates of interruption. Rates of substitution and switches to nonstandard regimen were lower in 2006-2009. Rates of modification and interruption were high, particularly in the first year of ART. Decreased rates of substitutions or switches to nonstandard regimen in recent years may be linked to greater use of well tolerated once-daily drugs.